2022
DOI: 10.1177/14644207221141768
|View full text |Cite|
|
Sign up to set email alerts
|

A review on β-Ti alloys for biomedical applications: The influence of alloy composition and thermomechanical processing on mechanical properties, phase composition, and microstructure

Abstract: Titanium and its alloys are potential materials for orthopedic implant applications due to their appropriate biological and mechanical behavior. As biocompatibility and biomechanical compatibilities are essential parameters for determining a biomedical implant's performance and service life, this research review article discussed the novel Ti alloys with nontoxic and biocompatible alloying elements with an elastic modulus similar to the bone. Among Ti alloys, β-Ti alloys are appropriate for load-bearing implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 249 publications
0
2
0
Order By: Relevance
“…It can be observed that the diffractograms presented characteristic The results of X-ray diffraction measurements for Ti-50Nb-xMo system samples are shown in Figure 6. It can be observed that the diffractograms presented characteristic peaks of a cubic structure of the centered body, which is typical of the β phase of this alloy [28][29][30][31]. Figure 8 presents the micrographs after melting; it is possible to perceive only the presence of the β phase of the Ti-50Nb-XMo system alloys, as already observed by Martins Jr et al [16] and Cardoso et al [32].…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…It can be observed that the diffractograms presented characteristic The results of X-ray diffraction measurements for Ti-50Nb-xMo system samples are shown in Figure 6. It can be observed that the diffractograms presented characteristic peaks of a cubic structure of the centered body, which is typical of the β phase of this alloy [28][29][30][31]. Figure 8 presents the micrographs after melting; it is possible to perceive only the presence of the β phase of the Ti-50Nb-XMo system alloys, as already observed by Martins Jr et al [16] and Cardoso et al [32].…”
Section: Resultssupporting
confidence: 63%
“…The results of X-ray diffraction measurements for Ti-50Nb-xMo system samples are shown in Figure 6 . It can be observed that the diffractograms presented characteristic peaks of a cubic structure of the centered body, which is typical of the β phase of this alloy [ 28 , 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…This consideration reflects the ongoing exploration of advanced materials to enhance the performance and longevity of biomedical implants in various orthopedic and dental applications. 2,26…”
Section: Low Elastic Modulusmentioning
confidence: 99%
“…The reduction of elastic modulus in metallic implants serves to mitigate bone atrophy arising from stress-shielding effects while concurrently enhancing the overall longevity and resilience of the implant. 1,2 The phenomenon known as the ‘stress shielding effect’ becomes inevitable when there is a disparity in the elastic modulus exists between the implant material and adjacent bone. 3 Wolff's law, a fundamental principle governing bone biology in healthy individuals or animals, posits that bones remodel and reconstruct in response to applied loads.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium alloys find extensive utilization in the field of biomedical devices due to their favorable characteristics, including low density, outstanding biocompatibility, exceptional resistance to corrosion, and impressive mechanical properties [1][2][3]. This is especially notable in load-bearing applications like orthopedic implants [3,4]. Among titanium alloys, Ti-6Al-7Nb has been successfully used in a range of clinical applications, including hip and knee implants, dental implants, and spinal implants and researchers have reported positive clinical outcomes with this alloy, including reduced complications and improved patient comfort [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%